The politics of defense revival in Argentina - Battaglino, Jorge Mario (2013)
Defense issues in Argentina have started to receive increasing political attention in the last few years. This new political interest contrasts markedly with what was happening in previous decades. In this way, the main goal of this article is to account for the new interest in defense policy. The article contends that this revival could be accounted by the implementation of a neo-developmentalist strategy as well as by the highest degree of exposure to defense issues that both presidents had during his political career. Both factors have promoted the implementation of policies that favored an increased of the military budget, the reconstruction of defense industry and the establishment of a new military doctrine. In this sense, the article analyzes how the neodevelopmentalist strategy and the prior policy experience of presidents have favored the revival of the defense agenda in Argentina after 2003. In this way, this article evaluates the impact of factors that were not previously considered by the literature on defense attention deficit in South America.